Profiling the US Sick Leave Landscape - Philip Susser; Nicolas R. Ziebarth (Institute for the Study of Labor (IZA), 2016)
This paper profiles the sick leave landscape in the US – the only industrialized country without universal access to paid sick leave or other forms of paid leave. We exploit the 2011 Leave Supplement of the American Time Use Survey (ATUS), a representative and comprehensive database on sick leave in the US. The two binary outcome variables measure (i) access to paid sick leave and (ii) suppressed sick leave ("presenteeism"). Thirty-five percent of US full-time employees lack access to paid sick leave. Low-income employees, service sector employees, and those in poor health have the lowest coverage rates. We estimate that, each week, up to three million US employees suppress their need for sick leave and engage in presenteeism behavior. These are primarily women with children and low-wage sector jobs.
Keywords: I12; I13; I18; J22; J28; J32; 330; gender inequality; low-income employees; unpaid leave; medical leave; paid leave; sick leave; presenteeism; US